A molybdenum-tungsten composite material and preparation method thereof

By using 10-16% tungsten molybdenum tungsten composite material in molybdenum wire, combined with three doping and sintering process optimization, the solid solution matrix of molybdenum tungsten alloy and pure tungsten particle structure is formed, which solves the problems of increased cost and deterioration of processing performance caused by the high tungsten doping amount in existing tungsten molybdenum alloy electrode wires, and achieves more efficient ablation resistance and longer service life.

CN119220875BActive Publication Date: 2025-02-28CHENGDU GREAT WALL TUNGSTEN & MOLYBDENUM NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411754738.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-28
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The tungsten doping amount in existing tungsten-molybdenum alloy electrode wires must reach 30-50 wt% or more to significantly improve the resistance to high-temperature ablation, but this leads to an increase in material cost and deterioration in processing performance, resulting in poor toughness of the electrode wire and easy to break wire.

Method used

The molybdenum-tungsten composite material with 10-16% tungsten is used to dopate lanthanum and tungsten into the molybdenum matrix material through three doping techniques, and optimized through the sintering process to form a solid solution matrix of molybdenum tungsten alloy and a diffuse distribution pure tungsten particle structure.

Benefits of technology

At lower tungsten doping, the material still has good processing properties and fracture toughness, which significantly improves the resistance to EDM and service life of the electrode wire, while reducing material costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220875B_ABST
    Figure CN119220875B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electrode wire technology. Aiming at the problem of excessive loss of composite doped molybdenum wire electrode wire, a molybdenum-tungsten composite material and a preparation method thereof are disclosed. The composite material comprises 10-16% tungsten and 0.1-0.15% lanthanum by mass fraction, and the remainder is molybdenum and inevitable impurity elements; and 5-12% tungsten and molybdenum form a molybdenum-tungsten alloy matrix, the remainder tungsten is pure tungsten particles, the molybdenum-tungsten alloy matrix is ​​a uniform molybdenum-tungsten alloy solid solution formed by tungsten and molybdenum, and the pure tungsten particles are pure tungsten dispersed in the molybdenum-tungsten alloy solid solution. The molybdenum-tungsten composite material proposed by the present invention comprises a molybdenum-tungsten alloy solid solution formed by tungsten and molybdenum, and pure tungsten particles dispersed in the molybdenum-tungsten alloy solid solution. In the subsequent discharge process, due to the tip effect, the discharge is mainly concentrated on the pure tungsten particle position with stronger ablation resistance. By utilizing the high melting point of tungsten, the loss of wire material of the electric spark wire cutting electrode wire during the discharge process can be reduced, and the service life of the electrode wire can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode wires, and in particular to a molybdenum-tungsten composite material and a preparation method thereof. Background Art

[0002] Molybdenum wire is widely used as the electrode wire of wire-cutting and high-speed wire-cutting machines. With the development of wire-cutting technology and the changes in application requirements, there are higher requirements for the anti-corrosion ability, loss, service life and other properties of wire-cutting molybdenum wire.

[0003] To improve the performance of molybdenum wire, it is necessary to dope other high-performance elements or substances to form a composite wire with better comprehensive performance. In view of the main problem of molybdenum wire electrode, that is, the melting point and recrystallization temperature of molybdenum are relatively low, and it is easy to be ablated by high temperature during the electric spark discharge process, resulting in rapid loss and short service life, the performance can usually be improved by doping with high-melting-point tungsten. For example, the patent with publication number CN111763862A provides a tungsten-molybdenum alloy and its preparation method, which is mainly made by mixing and sintering tungsten and molybdenum powder to make tungsten-molybdenum alloy for wire cutting processing electrode wire, which has the advantages of high temperature resistance, strong ablation resistance and long service life.

[0004] Among them, in the existing tungsten-molybdenum alloy electrode wire, the tungsten doping amount usually needs to reach 30-50wt% or more to make it play a significant role in high-temperature ablation resistance. For example, the patent with publication number CN111763862A provides a tungsten-molybdenum alloy and its preparation method, which includes about 30-50wt% tungsten. However, a higher tungsten doping amount will bring the following problems:

[0005] First, the cost increases. The higher the tungsten content, the higher the melting point of the molybdenum-tungsten alloy, and the better the ablation resistance of the corresponding material. However, the density of tungsten is about twice that of molybdenum. The increase in tungsten content will inevitably lead to an increase in the density of the alloy, thereby increasing the weight of the wire per unit length, which in turn leads to an increase in material costs.

[0006] Second, it is difficult to process. Tungsten has poor plasticity, and the plasticity of the solid solution alloy formed with molybdenum is worse than that of molybdenum. The higher the tungsten content, the worse the plasticity of the molybdenum-tungsten alloy, and the more difficult it is to process. The electrode wire processed into 0.18mm has poor toughness and is easy to break during use. It has a great adverse impact on production costs and actual use. Summary of the invention

[0007] The technical problems to be solved by the present invention are:

[0008] At present, in order to improve the high-temperature ablation resistance of molybdenum wire electrode wire, tungsten elements with a high melting point are usually doped into the molybdenum wire. However, in the existing tungsten-molybdenum alloy electrode wire, the tungsten doping amount usually needs to reach 30-50wt% or more to enable it to exert a significant high-temperature ablation resistance effect. However, a higher tungsten doping amount will increase the material cost per unit length of the electrode wire, and due to the deterioration of processing performance, the toughness of the 0.18mm electrode wire is poor, and the wire is prone to breakage during use, which has a significant adverse impact on production costs and actual use.

[0009] The technical solution adopted by the present invention is:

[0010] The present invention provides a molybdenum-tungsten composite material, which comprises 10-16% tungsten and 0.13% lanthanum, with the remainder being molybdenum and inevitable impurity elements, by mass fraction; and the tungsten comprises a molybdenum-tungsten alloy matrix and pure tungsten particles, the molybdenum-tungsten alloy matrix is ​​a molybdenum-tungsten alloy solid solution formed by tungsten and molybdenum, and the pure tungsten particles are pure tungsten dispersed in the molybdenum-tungsten alloy solid solution.

[0011] Preferably, in the molybdenum-tungsten composite material, by mass fraction, 5-12% of tungsten exists in the molybdenum-tungsten alloy solid solution, and the remainder of tungsten is pure tungsten particles.

[0012] Preferably, the diameter of the pure tungsten particles is 30-120 μm.

[0013] The present invention also provides a method for preparing the molybdenum-tungsten composite material, comprising the following steps:

[0014] S1 Lanthanum doping: Molybdenum dioxide and lanthanum nitrate solutions are taken separately, and solid-liquid doping is adopted to mix the molybdenum dioxide and lanthanum nitrate solutions, and heat and dry them to obtain lanthanum-doped molybdenum dioxide;

[0015] S2 Tungsten doping: Take ammonium metatungstate solution separately, adopt solid-liquid doping, mix lanthanum-doped molybdenum dioxide with the ammonium metatungstate solution, heat and dry, and sieve to obtain composite doped molybdenum dioxide powder;

[0016] S3 Reduction: placing the composite doped molybdenum dioxide powder in a reduction furnace, introducing hydrogen, performing reduction treatment, and screening to obtain lanthanum-doped molybdenum-tungsten alloy powder;

[0017] S4 Pure tungsten doping: pure tungsten powder is taken and mixed with lanthanum-doped molybdenum-tungsten alloy powder to obtain composite-doped molybdenum powder;

[0018] S5 Pressing and sintering: Pressing the composite-doped molybdenum powder into a blank, sintering it in a hydrogen protective atmosphere, and cooling it to obtain the molybdenum-tungsten composite material.

[0019] Preferably, in step S1, the molybdenum dioxide has a Fisher particle size of 4-8 μm and a purity greater than 99.95%; the mass concentration of the lanthanum nitrate solution is 2.6-2.79%; and the solid-liquid mass ratio after mixing is 18-25:1, preferably 24:1.

[0020] Preferably, in step S2, the mass concentration of tungsten element in the ammonium metatungstate solution is 20-37.51%, and the solid-liquid mass ratio during mixing is 6:1.

[0021] Preferably, in step S1 and / or step S2, the temperature for heating and drying after mixing is 110-150° C., and the drying time is 3-5 hours.

[0022] Preferably, in step S3, after reduction treatment, the powder has a Fischer-Tropsch particle size of 2.8-3.0 μm; in step S4, the pure tungsten powder has a Fischer-Tropsch particle size of 1.8-2.0 μm, a purity greater than 99.95%, and a mass proportion of the pure tungsten powder of 6-9%.

[0023] Preferably, in step S5, the pressing pressure is 180-200 MPa, and the pressure is maintained for 100-150 seconds; the sintering temperature is 1820-1880° C., and the sintering time is 3-5 hours.

[0024] The beneficial effects of the present invention are as follows:

[0025] The molybdenum-tungsten composite material of the present invention includes a molybdenum-tungsten alloy solid solution formed by tungsten and molybdenum, and pure tungsten particles dispersed in the molybdenum-tungsten alloy solid solution. Specifically, three doping processes are adopted to respectively dope elements such as lanthanum and tungsten into the molybdenum matrix material. By adjusting the doping process, the mutual diffusion of molybdenum and tungsten metals during the sintering process is reduced, and further combined with the optimization of the sintering process, the molybdenum-tungsten composite material containing the molybdenum-tungsten alloy solid solution and pure tungsten particles and their distribution structure is formed. The tungsten content in the matrix material is relatively low, and it still has good processing performance; the pure tungsten particles in the material have a higher melting point and ablation resistance. Due to the difference in the anti-ablation performance between the molybdenum-tungsten alloy solid solution matrix and the pure tungsten particles, the molybdenum-tungsten alloy solid solution matrix material is lost faster than the pure tungsten particles. After a period of discharge, as the molybdenum-tungsten alloy solid solution matrix is ​​lost, the pure tungsten particles are exposed, forming several protrusions on the wire surface; in the subsequent discharge process, due to the tip effect, the discharge is mainly concentrated on the pure tungsten particles with stronger ablation resistance, which greatly improves the material's anti-spark ablation ability and service life. That is, the present invention uses a lower doping amount of tungsten to reduce the wire loss of the electric spark wire cutting electrode wire during the discharge process, increase the service life of the electrode wire, reduce material costs, and improve processing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a metallographic scanning electron microscope image of the molybdenum-tungsten composite material in Example 1;

[0027] Figure 2 is the EDS layered diagram of the molybdenum-tungsten composite material in Example 1;

[0028] Figure 3 is the Mo element distribution diagram of the molybdenum-tungsten composite material in Example 1;

[0029] Figure 4 is a W element distribution diagram of the molybdenum-tungsten composite material in Example 1;

[0030] Figure 5 is the La element distribution diagram of the molybdenum-tungsten composite material in Example 1;

[0031] Figure 6 This is a graph showing the test results of the content of each element of the molybdenum-tungsten composite material in Example 1;

[0032] Figure 7 This is a metallographic scanning electron microscope image of the substrate of the molybdenum-tungsten composite material in Example 1;

[0033] Figure 8 for Figure 7 The test result diagram of each element content in the local area of ​​the molybdenum-tungsten composite material box;

[0034] Fig. 9 The metallographic scanning electron microscope image of the molybdenum-tungsten alloy in Comparative Example 2;

[0035] Fig.10 This is the EDS layer diagram of the molybdenum-tungsten alloy in Comparative Example 2. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0037] The present invention provides a molybdenum-tungsten composite material, which comprises, by mass fraction, 10-16% of tungsten and 0.1-0.15% of lanthanum, with the remainder being molybdenum and inevitable impurity elements;

[0038] Among them, tungsten includes a molybdenum-tungsten alloy matrix and pure tungsten particles. The molybdenum-tungsten alloy matrix is ​​a molybdenum-tungsten alloy solid solution formed by tungsten and molybdenum. The pure tungsten particles are pure tungsten with a diameter of about 30-120μm dispersed in the molybdenum-tungsten alloy solid solution, and the pure tungsten particles form a metallurgical bond with the molybdenum-tungsten alloy solid solution. Among them, in the molybdenum-tungsten composite material, 5-12% of the tungsten exists in the molybdenum-tungsten alloy solid solution, and the remainder of the tungsten exists in the form of pure tungsten particles.

[0039] In the present invention, the molybdenum-tungsten alloy solid solution matrix with low tungsten content has good plasticity and can maintain good toughness after being processed into wire material. Pure tungsten particles have a higher melting point and ablation resistance, which can reduce the molybdenum wire material loss of the electric spark wire cutting electrode wire during the discharge process, that is, increase the service life of the molybdenum-tungsten composite material when used as an electrode wire.

[0040] The molybdenum-tungsten composite material of the present invention can give full play to the performance advantages of tungsten and molybdenum. Among them, the matrix material has good toughness and processing performance, and pure tungsten has good ablation resistance. The molybdenum-tungsten composite material is plastically processed and drawn into wires of a size of φ0.18 mm. When used as an electrode wire for electric spark wire cutting, it has good processing performance, excellent ablation resistance and a long service life, has strong practicality and promotion, and can generate high economic value.

[0041] The present invention also provides a method for preparing the molybdenum-tungsten composite material, comprising the following steps:

[0042] (1) Lanthanum nitrate doping

[0043] Take high-purity molybdenum dioxide with a Fisher particle size of 4-8 μm and a purity greater than 99.95%, load it into a double-cone mixer, and control the filling amount to be 50-65% (by volume fraction); separately prepare a lanthanum nitrate solution with a lanthanum element mass concentration of 2.6-2.79%, add the lanthanum nitrate solution into the double-cone mixer in the form of a spray, and control the solid-liquid mass ratio during the addition to be 18-25:1 (more preferably 24:1), mix for 3-8 hours, and set the double-cone speed during mixing to 20-30 r / min; after the mixing is completed, place the mixture in an environment of 110-150° C. for drying for 3-5 hours to obtain lanthanum-doped molybdenum dioxide.

[0044] Lanthanum is doped into molybdenum dioxide by solid-liquid doping. By adjusting the solid-liquid mass ratio, a large amount of lanthanum, molybdenum and tungsten composite oxides are produced in the reduced molybdenum powder and evenly distributed in the composite powder. During the subsequent sintering process, the composite oxide can greatly activate the sintering process and make the grains grow rapidly, thereby reducing the sintering temperature and shortening the sintering time, thereby reducing the mutual diffusion of tungsten and molybdenum during the subsequent sintering process.

[0045] (2) Ammonium metatungstate doping

[0046] An ammonium metatungstate solution with a tungsten element mass concentration of 20-37.51% is prepared, and the ammonium metatungstate solution is added to the double cone mixer containing the above-mentioned lanthanum-doped molybdenum dioxide in the form of a spray, and the solid-liquid mass ratio in the double cone mixer during the addition is controlled to be 6:1, and the mixture is mixed again for 3-8 hours, and the double cone speed is maintained at 20-30r / min; after the mixing is completed, it is placed in an environment of 110-150°C for drying for 3-5 hours, and sieved through an 80-mesh sieve to obtain a composite doped molybdenum dioxide powder.

[0047] About half or more of the tungsten in the molybdenum-tungsten composite material of the present invention comes from the solid-liquid doping in this step, and in the subsequent reduction treatment, a lanthanum-doped molybdenum-tungsten alloy powder with a required Fisher particle size is formed.

[0048] (3) Restoration

[0049] The composite doped molybdenum dioxide powder is loaded into a boat, pushed into a reduction furnace, and hydrogen is introduced for reduction treatment, and then sieved through a 200-mesh sieve to obtain lanthanum-doped molybdenum-tungsten alloy powder;

[0050] Among them, the thickness of the material layer in the boat is 18-25mm;

[0051] The reduction furnace is divided into five temperature zones. From the feed end to the discharge end, the temperature ranges of the five temperature zones are 600-820°C, 750-950°C, 800-950°C, 850-1000°C, and 900-1050°C, respectively. Those skilled in the art can adjust the number of temperature zones, boat thickness, hydrogen flow rate, temperature range, etc. according to actual conditions to control the powder's Fisher particle size to be 2.8-3.0 μm.

[0052] During the reduction process, the hydrogen purity is 99.99%, the hydrogen dew point is -50℃, and the hydrogen flow rate is 14-25m 3 / h, hydrogen pressure in the furnace ≤5000pa.

[0053] (4) Tungsten doping

[0054] Take lanthanum-doped molybdenum-tungsten alloy powder, add 6-9% by mass of pure tungsten powder, mix; put it into a mixer according to a filling amount of 50-65% (by volume fraction), mix it, and obtain composite doped molybdenum powder;

[0055] Among them, the pure tungsten powder has a Fisher particle size of 1.8-2.0μm, a purity greater than 99.95%, and the content of impurity elements meets the requirements of GB / T3458 2006 "Tungsten Powder".

[0056] In this process, the control of the lanthanum-doped molybdenum tungsten alloy powder's Fisher particle size and the matching of the tungsten powder's Fisher particle size are to avoid the production of raw materials due to the different sintering activities of tungsten powder and lanthanum-doped molybdenum tungsten alloy powder and the asynchronous sintering densification process.

[0057] During the sintering process, pure tungsten and pure molybdenum are easy to diffuse into each other due to the large concentration difference at high temperature to form a uniform molybdenum-tungsten alloy solid solution; by solid-doping a part of tungsten in the form of pure tungsten into the lanthanum-doped molybdenum-tungsten alloy powder, during high-temperature sintering, the diffusion rate is slow due to the relatively small concentration difference between pure tungsten and molybdenum-tungsten alloy, so that the pure tungsten particles can be retained.

[0058] (5) Pressing and sintering

[0059] The composite-doped molybdenum powder is placed under a pressure of 180-200 MPa for 100-150 seconds and pressed into a billet; then sintered in a hydrogen protective atmosphere at a sintering temperature of 1820-1880°C for 3-5 hours; and then cooled to room temperature to obtain a molybdenum-tungsten composite material.

[0060] On the basis of the above three doping treatments, the diffusion process of pure tungsten particles can be slowed down by sintering at a lower temperature, so that the pure tungsten particles can be retained.

[0061] The preparation method of the molybdenum-tungsten composite material provided by the present invention adopts three-step doping to respectively dope elements such as lanthanum and tungsten into the molybdenum matrix material, and by adjusting the doping process and further optimizing the sintering process, a molybdenum-tungsten composite material having the above-mentioned specific bonding method can be obtained.

[0062] Example 1

[0063] Step 1: Take 119.83kg of high-purity molybdenum dioxide, measure its Fisher particle size to be 5.5μm and purity to be 99.96%, and put it into a spray double-cone mixer, the volume of molybdenum dioxide accounts for about 60% of the volume of the inner cavity of the mixer; separately prepare a lanthanum nitrate solution with a lanthanum element mass concentration of 2.60%, and add 5kg of lanthanum nitrate solution to the double-cone mixer containing molybdenum dioxide in the form of a spray at a solid-liquid mass ratio of 24:1, set the double-cone speed to 25r / min, and mix for 5h; after the mixing is completed, take out the material, place it in a 135°C environment for drying for 4h, and obtain lanthanum-doped molybdenum dioxide.

[0064] Step 2: Load the prepared lanthanum-doped molybdenum dioxide into a double cone mixer; prepare an ammonium metatungstate solution, determine the mass concentration of tungsten element therein to be 20.00%, and add the ammonium metatungstate solution to the double cone mixer containing lanthanum-doped molybdenum dioxide in the same spray form according to the solid-liquid mass ratio of 6:1, set the double cone speed to 20r / min, and mix for 5h; after mixing, take out the material, dry it in an environment of 120°C for 4h, and sieve it with an 80-mesh sieve to obtain a composite doped molybdenum dioxide powder.

[0065] Step 3: Load the composite doped molybdenum dioxide powder into a boat with a material layer thickness of 20 mm, push it into the reduction furnace, and introduce hydrogen with a purity of more than 99.99%, a dew point of -50 °C, and a flow rate of 20 ± 2 m 3 / h, controlling the hydrogen pressure in the furnace ≤5000pa; adjusting the temperatures of the five temperature zones in the reduction furnace to 700±10℃, 850±10℃, 870±10℃, 950±10℃, and 1020±10℃, respectively, for reduction treatment, and then sieving with a 200-mesh sieve to obtain lanthanum-doped molybdenum-tungsten alloy powder, and its Fisher particle size was measured to be 2.85μm.

[0066] Step 4: Take another high-purity tungsten powder with a Fisher particle size of 1.86 μm and a purity greater than 99.95%, and mix the high-purity tungsten powder and the lanthanum-doped molybdenum-tungsten alloy powder in a double-cone mixer, wherein the mass proportion of the high-purity tungsten powder is 6.00%, and the composite-doped molybdenum powder is obtained after mixing.

[0067] Step 5: Place the composite-doped molybdenum powder under 180MPa and hold the pressure for 120s to press it into a billet; then place the billet in a hydrogen protective atmosphere for sintering at a sintering temperature of 1850±20℃, sinter and hold for 4h, and then cool to room temperature to obtain a molybdenum-tungsten composite material.

[0068] Step 6: The molybdenum-tungsten composite material is subjected to plastic processing such as rolling, rotary forging, and drawing to produce an electrode wire with a thickness of 0.18 mm for electric spark wire cutting.

[0069] Example 2

[0070] Step 1: Take 114.49 kg of high-purity molybdenum dioxide, determine its Fisher particle size to be 6 μm and its purity to be 99.96%, and load it into a spray double-cone mixer, the volume of molybdenum dioxide accounting for about 60% of the volume of the inner cavity of the mixer; prepare a lanthanum nitrate solution with a lanthanum element mass concentration of 2.73%, and add 4.77 kg of lanthanum nitrate solution to the double-cone mixer containing molybdenum dioxide in the form of a spray at a solid-liquid mass ratio of 24:1, set the double-cone speed to 25 r / min, and mix for 5 hours; after the mixing is completed, take out the material, place it in a 135°C environment for drying for 4 hours, and obtain lanthanum-doped molybdenum dioxide.

[0071] Step 2: The prepared lanthanum-doped molybdenum dioxide is loaded into a double cone mixer; an ammonium metatungstate solution is prepared, and the mass concentration of tungsten element is determined to be 31.41%. The ammonium metatungstate solution is added to the double cone mixer containing lanthanum-doped molybdenum dioxide in the same spray form according to the solid-liquid mass ratio of 6:1, and the double cone speed is set to 20r / min, and the mixing treatment is performed for 5h; after the mixing is completed, the material is taken out, placed in an environment of 120°C for drying for 4h, and sieved with an 80-mesh sieve to obtain a composite doped molybdenum dioxide powder.

[0072] Step 3: Load the composite doped molybdenum dioxide powder into a boat with a material layer thickness of 18 mm, push it into the reduction furnace, and introduce hydrogen with a purity of more than 99.99%, a dew point of -50 °C, and a flow rate of 20 ± 2 m 3 / h, controlling the hydrogen pressure in the furnace ≤5000pa; adjusting the temperatures of the five temperature zones in the reduction furnace to 700±10℃, 850±10℃, 890±10℃, 980±10℃, and 1030±10℃, respectively, for reduction treatment, and then sieving with a 200-mesh sieve to obtain lanthanum-doped molybdenum-tungsten alloy powder, and its Fisher particle size was measured to be 2.9μm.

[0073] Step 4: Take another high-purity tungsten powder with a Fisher particle size of 1.94 μm and a purity greater than 99.95%, and mix the high-purity tungsten powder and the lanthanum-doped molybdenum-tungsten alloy powder in a double-cone mixer, wherein the mass proportion of the high-purity tungsten powder is 8.00%, and after mixing, the composite-doped molybdenum powder is obtained.

[0074] Step 5: Place the composite-doped molybdenum powder under 180MPa and hold the pressure for 120s to press it into a billet; then place the billet in a hydrogen protective atmosphere for sintering at a sintering temperature of 1850±20℃, sinter and hold for 4h, and then cool to room temperature to obtain a molybdenum-tungsten composite material.

[0075] Step 6: The molybdenum-tungsten composite material is subjected to plastic processing such as rolling, rotary forging, and drawing to produce an electrode wire with a thickness of 0.18 mm for electric spark wire cutting.

[0076] Example 3

[0077] Step 1: Take 126.49 kg of high-purity molybdenum dioxide, determine its Fisher particle size to be 6 μm and its purity to be 99.96%, and load it into a spray double-cone mixer, the volume of molybdenum dioxide accounting for about 60% of the volume of the inner cavity of the mixer; prepare a lanthanum nitrate solution with a lanthanum element mass concentration of 2.47%, and add 5.27 kg of lanthanum nitrate solution to the double-cone mixer containing molybdenum dioxide in the form of a spray at a solid-liquid mass ratio of 24:1, set the double-cone speed to 28 r / min, and mix for 5 hours; after the mixing is completed, take out the material, place it in a 135°C environment for drying for 4 hours, and obtain lanthanum-doped molybdenum dioxide.

[0078] Step 2: The prepared lanthanum-doped molybdenum dioxide is loaded into a double cone mixer; an ammonium metatungstate solution is prepared, and the mass concentration of tungsten element is determined to be 23.69%. The ammonium metatungstate solution is added to the double cone mixer containing lanthanum-doped molybdenum dioxide in the same spray form according to the solid-liquid mass ratio of 6:1, and the double cone speed is set to 20r / min, and the mixing treatment is performed for 5h; after the mixing is completed, the material is taken out, placed in an environment of 120°C for drying for 4h, and sieved with an 80-mesh sieve to obtain a composite doped molybdenum dioxide powder.

[0079] Step 3: Load the composite doped molybdenum dioxide powder into a boat with a material layer thickness of 18 mm, push it into the reduction furnace, and introduce hydrogen with a purity of more than 99.99%, a dew point of -50 °C, and a flow rate of 20 ± 2 m 3 / h, controlling the hydrogen pressure in the furnace ≤5000pa; adjusting the temperatures of the five temperature zones in the reduction furnace to 700±10℃, 850±10℃, 900±10℃, 980±10℃, and 1050±10℃, respectively, for reduction treatment, and then sieving with a 200-mesh sieve to obtain lanthanum-doped molybdenum-tungsten alloy powder, and its Fisher particle size was measured to be 2.92μm.

[0080] Step 4: Take another high-purity tungsten powder with a Fisher particle size of 1.96 μm and a purity greater than 99.95%, and mix the high-purity tungsten powder and the lanthanum-doped molybdenum-tungsten alloy powder in a double-cone mixer, wherein the mass proportion of the high-purity tungsten powder is 9.00%, and after mixing, the composite-doped molybdenum powder is obtained.

[0081] Step 5: Place the composite-doped molybdenum powder under 180MPa and hold the pressure for 120s to form a billet; then place the billet under a hydrogen protective atmosphere for sintering at a sintering temperature of 1860±20°C for 5h, and then cool to room temperature to obtain a molybdenum-tungsten composite material.

[0082] Step 6: The molybdenum-tungsten composite material is subjected to plastic processing such as rolling, rotary forging, and drawing to produce an electrode wire with a thickness of 0.18 mm for electric spark wire cutting.

[0083] Comparative Example 1

[0084] Step 1: Take 111.83 kg of high-purity molybdenum dioxide, determine its Fisher particle size to be 6 μm and its purity to be 99.96%, and load it into a spray double-cone mixer, the volume of molybdenum dioxide accounting for about 60% of the volume of the inner cavity of the mixer; prepare a lanthanum nitrate solution with a lanthanum element mass concentration of 2.79%, and add 4.66 kg of lanthanum nitrate solution to the double-cone mixer containing molybdenum dioxide in the form of a spray at a solid-liquid mass ratio of 24:1, set the double-cone speed to 28 r / min, and mix for 5 hours; after mixing, take out the material, place it in a 135°C environment for drying for 4 hours, and obtain lanthanum-doped molybdenum dioxide.

[0085] Step 2: The prepared lanthanum-doped molybdenum dioxide is loaded into a double cone mixer; an ammonium metatungstate solution is prepared, and the mass concentration of tungsten element is determined to be 37.51%. The ammonium metatungstate solution is added to the double cone mixer containing lanthanum-doped molybdenum dioxide in the same spray form according to the solid-liquid mass ratio of 6:1, and the double cone speed is set to 20r / min, and the mixing treatment is performed for 5h; after the mixing is completed, the material is taken out, placed in a 120°C environment for drying for 4h, and sieved with an 80-mesh sieve to obtain a composite doped molybdenum dioxide powder.

[0086] Step 3: Load the composite doped molybdenum dioxide powder into a boat with a material layer thickness of 18 mm, push it into the reduction furnace, and introduce hydrogen with a purity of more than 99.99%, a dew point of -50 °C, and a flow rate of 20 ± 2 m 3 / h, controlling the hydrogen pressure in the furnace ≤5000pa; adjusting the temperatures of the five temperature zones in the reduction furnace to 700±10℃, 850±10℃, 890±10℃, 980±10℃, and 1030±10℃, respectively, for reduction treatment, and then sieving with a 200-mesh sieve to obtain lanthanum-doped molybdenum-tungsten alloy powder, and its Fisher particle size was measured to be 2.86μm.

[0087] Step 4: Place the lanthanum-doped molybdenum-tungsten alloy powder under 180MPa and hold the pressure for 120s to form a billet; then place the billet under a hydrogen protective atmosphere for sintering at a sintering temperature of 1860±20°C for 5h, and then cool to room temperature to obtain a molybdenum-tungsten composite material.

[0088] Step 5: The prepared material is subjected to plastic processing such as rolling, rotary forging, and drawing to produce an electrode wire with a thickness of 0.18 mm for electric spark wire cutting.

[0089] Comparative Example 2

[0090] Step 1: Take 99.83kg of high-purity molybdenum dioxide, determine its Fisher particle size to be 6μm and its purity to be 99.96%, and load it into a spray double-cone mixer, the volume of molybdenum dioxide accounts for about 60% of the volume of the inner cavity of the mixer; prepare a lanthanum nitrate solution with a lanthanum element mass concentration of 3.13%, and add 4.16kg of lanthanum nitrate solution to the double-cone mixer containing molybdenum dioxide in the form of a spray at a solid-liquid mass ratio of 24:1, set the double-cone speed to 28r / min, and mix for 5h; after mixing, take out the material, place it in a 135°C environment for drying for 4h, and obtain lanthanum-doped molybdenum dioxide.

[0091] Step 2: Put the lanthanum-doped molybdenum dioxide powder into a boat with a material layer thickness of 18 mm, push it into the reduction furnace, and introduce hydrogen with a purity of more than 99.99%, a dew point of -50°C, and a flow rate of 20±2m 3 / h, controlling the hydrogen pressure in the furnace ≤5000pa; adjusting the temperatures of the five temperature zones in the reduction furnace to 700±10℃, 850±10℃, 880±10℃, 950±10℃, and 980±10℃, respectively, for reduction treatment, and then sieving with a 200-mesh sieve to obtain lanthanum-doped molybdenum-tungsten alloy powder, and its Fisher particle size was measured to be 2.94μm.

[0092] Step 3: Take another high-purity tungsten powder with a Fisher particle size of 1.88 μm and a purity greater than 99.95%, and mix the high-purity tungsten powder and the lanthanum-doped molybdenum-tungsten alloy powder in a double-cone mixer, wherein the mass proportion of the high-purity tungsten powder is 25.00%, and after mixing, the composite-doped molybdenum powder is obtained.

[0093] Step 4: Place the composite-doped molybdenum powder under 190MPa and hold the pressure for 120s to form a billet; then place the billet under a hydrogen protective atmosphere for sintering at a sintering temperature of 1880±20°C for 5h, and then cool to room temperature to obtain a molybdenum-tungsten composite material.

[0094] Step 5: The molybdenum-tungsten composite material is subjected to plastic processing such as rolling, rotary forging, and drawing to produce an electrode wire with a thickness of 0.18 mm for electric spark wire cutting.

[0095] Comparative Example 3

[0096] Step 1: Take 60kg of high-purity molybdenum powder with a Fischer-Tropsch particle size of 2.9μm and a purity greater than 99.95% and 40kg of high-purity tungsten powder with a Fischer-Tropsch particle size of 1.98μm and a purity greater than 99.95%, place the two powders in a double cone mixer and mix them to obtain tungsten-doped molybdenum powder.

[0097] Step 2: Place the tungsten-doped molybdenum powder under 190 MPa and hold the pressure for 120 seconds to press it into a billet; then place the billet in a hydrogen protective atmosphere for sintering at a sintering temperature of 1920±20°C for 5 hours, and then cool it to room temperature to obtain the prepared material.

[0098] Step 3: The material is subjected to plastic processing such as rolling, rotary forging, and drawing to produce an electrode wire with a thickness of 0.18 mm for electric spark wire cutting.

[0099] Test example

[0100] Samples: Examples 1-3, Comparative Examples 1-3

[0101] (1) Metallographic observation

[0102] like Figure 1 As shown, the molybdenum-tungsten composite material in Example 1, wherein the powder is pressed and sintered to form a relatively dense metal; Figures 2 to 5 From the EDS layered diagrams of different elements shown, it can be found that the lanthanum element is evenly distributed in the material, but the tungsten and molybdenum are unevenly distributed. In most areas, tungsten and molybdenum form a uniform solid solution alloy. The local areas without green and dark purple are pure tungsten particles, which are metallurgically bonded to the matrix. Figures 6 to 8 The content of each element in different parts is shown. It can be found that in the matrix position (combined with Figure 2 and Figure 7Tungsten and molybdenum form a uniform solid solution alloy (as shown in the box), in which the tungsten content is about 10%, the molybdenum content is about 89.88%, and the lanthanum content is about 0.12%.

[0103] Fig. 9 and Fig.10 Shown are the metallographic scanning electron microscope images of the metal material prepared in Comparative Example 2 and the EDS layered images of different elements. It can be found that the molybdenum and tungsten in the material prepared by this method have formed a uniform molybdenum-tungsten solid solution alloy, and the tungsten, molybdenum and lanthanum elements are evenly distributed.

[0104] according to Figures 1 to 10 The scanning electron microscope image and EDS layered image shown in the figure can confirm that the molybdenum-tungsten composite material prepared by the present invention can form a molybdenum-tungsten alloy solid solution matrix formed by tungsten and molybdenum, and the tungsten-molybdenum alloy solid solution matrix is ​​dispersed with pure tungsten particles. When prepared by other methods, even if 25% tungsten is added, tungsten and molybdenum will form a continuous solid solution molybdenum-tungsten alloy during the sintering process.

[0105] (2) Performance testing

[0106] The electrode wires prepared in the manner of Examples 1-3 and Comparative Examples 1-3, wherein the types and doping amounts of the dopants are shown in Table 1 below; the processing conditions of 80 kg of each group of samples are shown in Table 2; the loss and service life of the electrode wires of the above samples are measured by tests such as electric spark wire cutting, and the results are shown in Table 3 below:

[0107] Table 1 Element contents of doped parts in different samples

[0108]

[0109] Table 2 Wire breakage during sample processing

[0110]

[0111] Table 3 Cutting performance of different φ0.18 mm wires

[0112]

[0113] As shown in Table 2 above, the molybdenum-tungsten composite materials prepared in Examples 1 to 3 still maintain good processing performance during rolling and drawing, and the number of wire breakage is equivalent to that of the tungsten-molybdenum alloy containing 5wt% tungsten in Comparative Example 1; while when the tungsten content of the tungsten-molybdenum alloy material prepared according to the traditional method increases, such as Comparative Examples 2 and 3, the number of wire breakage during processing increases significantly, and the processing performance deteriorates. This shows that the molybdenum-tungsten composite material proposed in the present invention still has good processing performance when the mass percentage of tungsten content is 10-16%.

[0114] As shown in Table 3 above, compared with Comparative Examples 1 and 2, the molybdenum-tungsten composite materials containing molybdenum-tungsten alloy solid solutions and dispersed pure tungsten particles in the solid solutions prepared in Examples 1 to 3 have a total cutting area of ​​150,000 mm and a surface area of ​​150,000 mm. 2 When the wire size is significantly larger, while the wire size remains the same when the wire is broken, it can be explained that the molybdenum-tungsten composite materials in Examples 1 to 3, when used as electrode wires and processed under the same working conditions, have significantly smaller breakage losses and longer cutting life. Compared with Comparative Example 3, the tungsten-molybdenum composite materials prepared in Examples 1 to 3 can cut 150,000 mm 2 The wire size is equivalent to that of comparative example 3, and the total cutting area is also not much different, which shows that the molybdenum-tungsten composite material proposed in the present invention can achieve the same anti-ablation performance at a lower tungsten doping amount and has certain economic benefits.

[0115] In summary, it is shown that the molybdenum-tungsten composite material for electrode wire proposed in the present invention can achieve a comparable high-temperature ablation resistance effect as well as good processing performance and fracture toughness resistance at a lower tungsten doping amount, and has good economic efficiency.

[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A molybdenum-tungsten composite material, characterized in that: Calculated by mass fraction, it includes 10-16% tungsten and 0.1-0.15% lanthanum, and the balance is molybdenum and inevitable impurity elements; and the tungsten includes a molybdenum-tungsten alloy matrix and pure tungsten particles. The molybdenum-tungsten alloy matrix is ​​a molybdenum-tungsten alloy solid solution formed by tungsten and molybdenum, and the pure tungsten particles are pure tungsten dispersed in the molybdenum-tungsten alloy solid solution.

2. The molybdenum-tungsten composite material according to claim 1, characterized in that: Calculated by mass fraction, in the molybdenum-tungsten composite material, 5-12% tungsten exists in the molybdenum-tungsten alloy solid solution, and the remaining tungsten is pure tungsten particles.

3. The molybdenum-tungsten composite material according to claim 1, characterized in that: The diameter of pure tungsten particles is 30-120μm.

4. A method for preparing the molybdenum-tungsten composite material according to any one of claims 1 to 3, characterized in that: The steps include: S1 Lanthanum doping: Molybdenum dioxide and lanthanum nitrate solutions are taken separately, and solid-liquid doping is adopted to mix the molybdenum dioxide and lanthanum nitrate solutions, and heat and dry them to obtain lanthanum-doped molybdenum dioxide; S2 Tungsten doping: Take ammonium metatungstate solution separately, adopt solid-liquid doping, mix lanthanum-doped molybdenum dioxide with the ammonium metatungstate solution, heat and dry, and sieve to obtain composite doped molybdenum dioxide powder; S3 Reduction: placing the composite doped molybdenum dioxide powder in a reduction furnace, introducing hydrogen, performing reduction treatment, and screening to obtain lanthanum-doped molybdenum-tungsten alloy powder; S4 Pure tungsten doping: pure tungsten powder is taken and mixed with lanthanum-doped molybdenum-tungsten alloy powder to obtain composite-doped molybdenum powder; S5 Pressing and sintering: Pressing the composite-doped molybdenum powder into a blank, sintering it in a hydrogen protective atmosphere, and cooling it to obtain the molybdenum-tungsten composite material.

5. The method for preparing the molybdenum-tungsten composite material according to claim 4, characterized in that: In step S2, the mass concentration of tungsten element in the ammonium metatungstate solution is 20-37.51%, and the solid-liquid mass ratio during mixing is 6:

1.

6. The method for preparing the molybdenum-tungsten composite material according to claim 4, characterized in that: In step S3, after reduction treatment, the powder has a Fisher particle size of 2.8-3.0 μm; In step S4, the pure tungsten powder has a Fisher particle size of 1.8-2.0 μm, a purity greater than 99.95%, and a mass proportion of the pure tungsten powder is 6-9%.

Citation Information

Patent Citations

  • Tungsten-molybdenum alloy and manufacturing method thereof

    CN111763862A

  • Method for preparing tungsten-molybdenum alloy by doping beneficial elements

    CN106591613A

  • Rare earth, molybdenum and tungsten alloy used for cutting wires and preparing method thereof

    CN110106418A